The calling of Katie Makanya, M. McCord : book review (Historia, 2021)
The calling of Katie Makanya is one of the most engrossing and heart-rendering books I have had the privilege of reading. It is the life story of Katie Makanya from her youth in the eastern Cape to her death at the age of 83 in 1955. It is based on interviews she had with Margaret McCord for whose father, Dr. James McCord, Katie had worked for 35 years as interpreter, dispenser and assistant in Natal.
Keywords: F.A. Mouton; Katie Makanya; Eastern Cape; Margaret McCord; Dr. James McCord; Natal; Queen Victoria; Britain; Jubilee Chorus; Lord Knutsford; ANC; Women's League; America